How accurate are forecasts of costs of energy? A methodological contribution. (December 2015) - Siddons, Craig; Allan, Grant; McIntyre, Stuart
Abstract: Forecasts of the cost of energy are typically presented as point estimates; however forecasts are seldom accurate, which makes it important to understand the uncertainty around these point estimates. The scale of the differences between forecasts and outturns (i.e. contemporary estimates) of costs may have important implications for government decisions on the appropriate form (and level) of support, modelling energy scenarios or industry investment appraisal. This paper proposes a methodology to assess the accuracy of cost forecasts. We apply this to levelised costs of energy for different generation technologies due to the availability of comparable forecasts and contemporary estimates, however the same methodology could be applied to the components of levelised costs, such as capital costs. The estimated "forecast errors" capture the accuracy of previous forecasts and can provide objective bounds to the range around current forecasts for such costs. The results from applying this method are illustrated using publicly available data for on- and off-shore wind, Nuclear and CCGT technologies, revealing the possible scale of "forecast errors" for these technologies. Abstract : Highlights: A methodology to assess the accuracy of forecasts of costs of energy is outlined. Method applied to illustrative data for four electricity generation technologies. Results give an objective basis for sensitivity analysis around point estimates.